IMPROVING TEACHER COMPETENCE IN DEVELOPING CLASS-BASED ASSESSMENT DESIGNS THROUGH TRAINING AND MENTORING AT IGABA WEDI SUB-DISTRICT, KLATEN REGENCY 2021 - Uswatun Khasanah; Badroh rif ati; Lukman Hakim (Bajang Institute, 2021)
Improving teacher competence in developing assessment designs during the COVID-19 period requires understanding. In this case, many efforts have been made to prepare teachers to become professionals. However, the reality shows that not all teachers have good competence in carrying out their duties. In addition, planning preparation, process implementation, and assessment are a complete series of educational programs and are an integral part that cannot be separated from one another. For this reason, there needs to be an assessment model that can be employed as a reference by teachers and organizers at the BA/RA/TK (early childhood education) level. Conditions, such as the one above that not all teachers can carry out assessments well, even rarely or do not conduct assessments except at end-semester or mid-semester examinations, are expected to change. Therefore, this community service was carried out to provide additional knowledge for teachers in improving teacher competence in preparing class-based assessment designs through training and mentoring. Activities were held in the form of training; participants were given the material and then practiced. After being given the training, 95% of the competent participants preparing the assessment designs gave a positive response, even asking for further training